66 Short Term Outcomes Following Fragility HIP Fracture in Malaysia. (20th December 2019) - Khor, Hui Min; Teh, Hui Xin; Tan, Fang Chin; Shanmugam, Tharshne; Kumar, Sankara C; Tan, Kit Mun; Singh, Simmrat; Saedon, Nor' Izzati; Chin, Ai Vyrn; Kamaruzzaman, Shahrul B; Tan, Maw Pin
Abstract: Introduction: Hip fracture carries huge burden to the older person with 40% of patients unable to walk independently after a year and mortality risk of 30% at one year. The study aims to report short-term outcomes following hip fracture from the experience of a tertiary center in Kuala Lumpur. Methods: A prospective study was performed in University of Malaya where consecutive patients admitted to the orthopaedic wards with fragility hip fracture from March 2016 to August 2018 were recruited. Information on basic socio-demographics, comorbidities, functional status, pre and post-operative assessments, and discharge details were recorded. Outcome measures include the ability to return to pre-fracture mobility status and mortality in 6 months post fracture. Results: A total of 302 patients with mean age of 79.8 (SD 7.28) years old were included in the study. 276 (91.4%) underwent surgery with mortality rate of 7% in 30days and 14.4% in 6 months. 16.4% of patients underwent surgery within 48hours of admission. Time to surgery was not associated with morbidity or mortality outcome in our study. In 6 months follow up, 23.6% of patients were freely mobile, 27.1% were mobile with one aid, 35.5% required walking frame and 13.8% were immobile. 41.6% of patients managed to regain prefracture mobility status. Multivariate analysis showed that age, length of hospitalization and prefracture mobility statuses were predictors of mobility recovery after hip fracture. Conclusion: Fragility hip fracture has devastating consequences from our study. There is an urgent call to improve acute hip fracture care and post-acute care rehabilitation in Malaysia.